PEMANFAATAN MEDIA SOSIAL DALAM PENJUALAN PRODUK SR12 PERSPEKTIF EKONOMI ISLAM (Studi Strategi Pemasaran Elsko Store Bengkulu) - Saputri, Ika; Mursalin, Supardi; Harpepen, Andi (JURNAL ILMIAH EDUNOMIKA, 2024)
The aim of this research is to determine the marketing strategy for selling SR12 products via social media from an Islamic economic perspective. The method used is a qualitative method with a qualitative descriptive approach. Data collection techniques use field research. The data type consists of primary data and secondary data. Data analysis is carried out by recording and interpreting it, then analyzing it using a deductive mindset. The research results show that the marketing strategy used by Elsko Store Bengkulu is First, the products sold include skincare/cosmetics, bodycare, herbal products and children's products. Second, guaranteeing the availability of goods is always ready stock. Third, the prices sold on social media are the same as the prices sold in stores because they follow the company's SOP. Fourth, use a shipping expedition to send consumer orders. Fifth, utilize social media such as WhatsApp, Facebook, Instagram and TikTok. In an Islamic economic perspective, the marketing strategy used meets the characteristics of sharia marketing, namely: Saleh (Rabbaniyah), Ethical (Akhlaqiyyah), Realistic (Al-Waqiiyyah) and Humanist. Keywords : Marketing Strategy, Social Media, Islamic Economy